2019
DOI: 10.1080/02643294.2019.1607272
|View full text |Cite
|
Sign up to set email alerts
|

Can the English stand the bottle like the Dutch? Effects of relational categories on object perception

Abstract: Does language influence how we perceive the world? This study examines how linguistic encoding of relational information by means of verbs implicitly affects visual processing, by measuring perceptual judgements behaviourally, and visual perception and attention in EEG. Verbal systems can vary cross-linguistically: Dutch uses posture verbs to describe inanimate object configurations (the bottle stands/lies on the table). In English, however, such use of posture verbs is rare (the bottle is on the table). Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…As we will show, the memorisation performance and eye-gazing analysed in our study confirm a subtle cognitive impact of the linguistic preferences in the domain of location described above (unlike Flecken & Van Bergen, 2019). In addition, our study shows that location can indeed not be seen as fully in parallel to motion, as it cuts across the typological boundaries and this does not find a satisfactory answer in Talmy's split systems.…”
Section: Figure-oriented Ground-orientedmentioning
confidence: 42%
See 1 more Smart Citation
“…As we will show, the memorisation performance and eye-gazing analysed in our study confirm a subtle cognitive impact of the linguistic preferences in the domain of location described above (unlike Flecken & Van Bergen, 2019). In addition, our study shows that location can indeed not be seen as fully in parallel to motion, as it cuts across the typological boundaries and this does not find a satisfactory answer in Talmy's split systems.…”
Section: Figure-oriented Ground-orientedmentioning
confidence: 42%
“…This cognitive impact of language-specific preferences on non-verbal conceptualisation is at the centre of the study reported on here. As such, we situate ourselves in the recent body of studies inspired by event integration theory, which have shown how languagespecific preferences in event descriptions do indeed impact attention allocation during event observation, memorisation, and categorisation (see, among others, Berman & Slobin, 1994;Bosse & Papafragou, 2010Bowerman & Choi, 2001Choi & Bowerman, 1991;Filipović, 2011;Flecken et al, 2015;Flecken & Van Bergen, 2019;Gennari et al, 2002;Hickmann, 2006;Landau & Jackendoff, 1993;Papafragou & Selimis, 2010;Slobin, 1996; for an account of bilinguals and learners, see, among others, Filipović, 2011Filipović, , 2018. Focusing on the conceptualisation of locative events, Flecken and Van Bergen (2019) investigate the cognitive impact of the probabilistic differences in the linguistic encoding of relational information in English and Dutch via a picture-matching task.…”
Section: Introduction: a Typology For Locative Eventsmentioning
confidence: 99%
“…Montero-Melis et al, 2017). Similarly, in a picture-matching study by Flecken and Van Bergen (2020), ERPs recorded from native English and Dutch participants for mismatching object configurations, also yielded no group differences in the P300 domain, likely due to probabilistic encoding of object position in English. In contrast, grammatical features are encoded more regularly and may have a stronger overall effect on event conceptualization and early attention (cf.…”
Section: Discussionmentioning
confidence: 81%
“…In the statistical analyses, the selections of time windows and electrodes were based on related prior oddball paradigm studies (Flecken, Athanasopoulos, et al, 2015; Flecken & Van Bergen, 2020) as well as visual inspection of the current data. We used 350–700 ms as the P300 time window.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation